Teaching Approach and Teacher Self-Efficacy during Early Childhood Distance Learning - Sibagariang, Pradita Permatasari; S. Pandia, Weny Savitry (Jurnal Pendidikan Usia Dini, 2021)
Child Distance Learning (CDL) during the pandemic has led to an optimal development of children and effective teaching and learning processes in kindergartens. To overcome this, teachers need to apply a teaching approach in accordance with the principles of kindergarten education. In addition, teachers' self-efficacy of their ability to teach is also important for developing children's skills. This study aims to describe the teaching approach and the efficacy of kindergarten teachers during the CDL process and to identify the relationship between the two. The research method used is quantitative through document analysis as a source of data findings. A total of 116 Public Kindergarten (PK) teachers in DKI Jakarta participated in filling out the Classroom Management Scale and Teachers' Sense of Efficacy Scale online. All data were processed using descriptive statistics and correlation. Furthermore, there is a document analysis carried out on the Daily / Weekly Learning Program Design in PK Jakarta. The findings identified that the teaching approach of kindergarten teachers during CDL included only two principles of kindergarten education, namely thematic teaching and developing life skills. Furthermore, PK teachers in the Jakarta area showed low self-efficacy during CDL. The teaching approach and self-efficacy were caused by teachers' unpreparedness in facing challenges during CDL. In addition, other findings indicate that there is a relationship between teaching approaches and teacher self-efficacy. Another CDL model Interventions to increase teacher self-efficacy and the extent to which the relationship between the two variables can be studied further in future studies. Keywords: Early Childhood, Distance Learning, Teaching Approach, Teacher Self-Efficacy References: Agustin, M., & Wahyudin, U. (2011). Penilaian perkembangan anak usia dini. Refika Aditama. Agustin, M., Puspita, R. D., Nurinten, D., & Nafiqoh, H. (2020). Tipikal Kendala Guru PAUD dalam Mengajar pada Masa Pandemi Covid 19 dan Implikasinya. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(1), 334. https://doi.org/10.31004/obsesi.v5i1.598 Ayu, N. (2015). Pengelolaan Kurikulum 2013 Di Tk Negeri Pembina Semarang. Program Sarjana Universitas Negeri Semarang. Bullock, A., Coplan, R. J., & Bosacki, S. (2015). Exploring links between early childhood educators’ psychological characteristics and classroom management self-efficacy beliefs. Canadian Journal of Behavioural Science, 47(2), 175–183. https://doi.org/10.1037/a0038547 Cheung, S. K., Fong, R. W. tsz, Leung, S. K. Y., & Ling, E. K. wei. (2019). The Roles of Hong Kong Preservice Early Childhood Teachers’ Creativity and Zest in Their Self-efficacy in Creating Child-centered Learning Environments. Early Education and Development, 30(6), 788–799. https://doi.org/10.1080/10409289.2019.1586224 Choi, J., Lee, J., & Kim, B. (2019). How does learner-centered education affect teacher self-efficacy? The case of project-based learning in Korea. Teaching and Teacher Education, 85, 45–57. Dimyati, J. (2016). Pembelajaran terpadu untuk taman kanak-kanak/ raudhatul athfal dan sekolah dasar. Prenamedia Group. Dinçer, Ç., & Akgün, E. (2015). Developing a classroom management skills inventory for preschool teachers and the correlation of preschool teachers’ classroom management skills with different variables. Egitim Ve Bilim, 40(117). Duffin, L., Patrick, H., & French, B. (2012). The teachers’ sense of efficacy scale: Confirming the factor structure with beginning pre-service teachers. Teaching and Teacher Education: An International Journal of Research and Studies, 28(6), 827–834. Essa, E. (2011). Introduction to early childhood education. Wadsworth. Harwati, D., & Mariyanti, S. (2014). Hubungan antara self-efficacy dengan burnout pada pengajar taman kanak-kanak sekolah “X” di Jakarta. Jurnal Psikologi, 12(2), 54–60. Ismawati, D., & Prasetyo, I. (2020). Efektivitas pembelajaran menggunakan video zoom cloud meeting pada anak usia dini era pandemi covid-19. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(1), 665-675. DOI: 10.31004/obsesi. v5i1.671 Jackman, H. (2011). Early education curriculum: A child’s connection to the world. Delmar Thomson Learning. Jalal, M. (2020). Kesiapan guru menghadapi pembelajaran jarak jauh di masa covid-19. Smart Kids: Jurnal Pendidikan Islam Anak Usa Dini, 2(1), 35–40. Johar, R., & Hanum, L. (2016). Strategi belajar mengajar. Penerbit Deepublish. Klassen, R. M., & Chiu, M. M. (2010). Effects on teachers’ self-efficacy and job satisfaction: Teacher gender, years of experience, and job stress. Journal of Educational Psychology, 102(3), 741–756. https://doi.org/10.1037/a0019237 Lee, C., & Davis, H. (2014). Teacher self-efficacy. In W. Scarlett (Ed.), The sage encyclopedia of classroom management (Vol. 2, pp. 811-812). SAGE Publications Inc., https://www.doi.org/10.4135/9781483346243.n341. Masdudi, M. (2016). Karakteristik perkembangan pendidikan anak usia dini. Jurnal Pendidikan Anak, 1(2), 1-26. Moran, M., & Hoy, A. (2001). Teacher efficacy: capturing an elusive construct. Teaching and Teacher Education, 17, 783-805. Mulyani, S., Nasution, E., & Pratiwi, I. (2020). Hubungan efikasi diri dan keterikatan kerja guru taman kanak-kanak. JP3SDM, 9(1), 74-89. Ndari., & Chandrawaty. (2018). Telaah kurikulum pendidikan anak usia dini. Edu Publisher. Nindiati, D. (2020). Pengelolaan pembelajaran jarak jauh yang memandirikan siswa dan implikasinya pada pelayanan pendidikan. Journal of Education and Instruction, 3(1), 14-20. Restyningtyas, D. (2013). Penerapan Child Centered pada Anak Usia Dini di Taman Anak (TA) Sanggar Anak Alam (SALAM). Fakultkas Ilmu Pendidikan Universitas Negeri Yogyakarta. Saifulloh, A. M., & Darwis, M. (2020). Manajemen pembelajaran dalam meningkatkan efektifikas proses belajar mengajar di masa pandemic covid-19. Jurnal Pendidikan Guru Madrasah Ibtidaiyah. 3(2). Saptaningrum, ernawati & wiwik, & refiane, fine. (2012). Model pembelajaran aktif kreatif efektif menyenangkan melalui pendekatan tematik untuk pembelajaran sains. Jurnal penelitian pembelajaran fisika. 2. 10.26877/jp2f.v2i1/april.125. Scarlett, W. (Ed.) (2014). The sage encyclopedia of classroom management. (Vols. 1-2). SAGE Publications Inc., https://www.doi.org/10.4135/9781483346243 Schweinhart, L. (2016). Child-initiated learning. In D. Couchenour, & J. Chrisman (Eds.), The sage encyclopedia of contemporary early childhood education (pp. 231-233). SAGE Publications, Inc, https://www.doi.org/10.4135/9781483340333.n61 Shaukat, S., & Iqbal, H. (2012). Teacher self-efficacy as a function of student engagement, instructional strategies, and classroom management. Pakistan Journal of Social and Clinical Psychology, 9(3), 82-85. Soedjono, 2008. Pembelajaran Sains Moderen. http://www.guru-scn/pakem.html. Syarah, E. S., Mayuni, I., & Dhieni, N. (2020). Understanding Teacher's Perspectives in Media Literacy Education as an Empowerment Instrument of Blended Learning in Early Childhood Classroom. Jurnal Pendidikan Usia Dini, 14(2), 201-214. Tiara, D. R., & Pratiwi, E. (2020). Mengukur Kesiapan Guru Sebagai Dasar Pembelajaran Daring Di Lembaga PAUD. Jurnal Golden Age, 4(02), 362-368. Utami, dkk. (2014). Modul PLPG pendidikan anak usia dini, Buku I. Konsorsium Sertifikasi Guru. Yusnita, N., & Muqowim. (2020). Pendekatan student centered learning dalam menanamkan karakter disiplin dan mandiri anak di TK Annur II. Jurnal Ilmiah Potentia, 5(2), 116–126.